2014
DOI: 10.1242/jeb.106344
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of extreme climatic events on the energetics of long-lived vertebrates: the case of the greater flamingo facing cold spells in the Camargue

Abstract: Most studies analyzing the effects of global warming on wild populations focus on gradual temperature changes, yet it is also important to understand the impact of extreme climatic events. Here we studied the effect of two cold spells (January 1985 and February 2012) on the energetics of greater flamingos (Phoenicopterus roseus) in the Camargue (southern France). To understand the cause of observed flamingo mass mortalities, we first assessed the energy stores of flamingos found dead in February 2012, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 58 publications
0
29
0
Order By: Relevance
“…Cold exposure can cause mortality of small passerines in winter, even in conditions that are relatively mild [17,22,44]. For example, prolonged exposure to cold wet weather with daily minima less than 58C was associated with high mortality in a range of similar-sized passerine species in Britain [23].…”
Section: Direct Effects Of Climate On Survivalmentioning
confidence: 99%
“…Cold exposure can cause mortality of small passerines in winter, even in conditions that are relatively mild [17,22,44]. For example, prolonged exposure to cold wet weather with daily minima less than 58C was associated with high mortality in a range of similar-sized passerine species in Britain [23].…”
Section: Direct Effects Of Climate On Survivalmentioning
confidence: 99%
“…Extreme cold events can also have similar fitness consequences. For example, greater flamingos, Phoenicopterus roseus, with lower body condition experienced mass starvation under the combined effect of lower than average winter temperatures and a cold spell that limited access to food [9].…”
Section: Introductionmentioning
confidence: 99%
“…With low temperatures, nonhibernating endotherms are confronted with increasing energy requirements to enhance thermogenesis while food is a scarce resource (Boos et al 2007, Deville et al 2014. In many bird species it has thus been shown that winter conditions such as low temperatures or consecutive frosts influence survival (e.g., Deville et al 2014, Johnston et al 2016.…”
Section: Winter Survival Ratementioning
confidence: 99%
“…With low temperatures, nonhibernating endotherms are confronted with increasing energy requirements to enhance thermogenesis while food is a scarce resource (Boos et al 2007, Deville et al 2014. In many bird species it has thus been shown that winter conditions such as low temperatures or consecutive frosts influence survival (e.g., Deville et al 2014, Johnston et al 2016. In France, a negative relationship between winter temperature and woodcock survival was also found, as well as escape behavior below a certain temperature threshold (Tavecchia et al 2002, Péron et al 2011a, presumably because dealing with such conditions would be riskier than moving away from their usual wintering areas (Duriez 2003).…”
Section: Winter Survival Ratementioning
confidence: 99%